2002
DOI: 10.1302/0301-620x.84b2.12143
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical reconstruction and Evans tenodesis of the lateral ligaments of the ankle: Clinical and radiological findings after follow-up for 15 to 30 years

Abstract: In this retrospective study, we assessed the outcome in 99 patients who underwent reconstruction of the lateral ligaments of the ankle for chronic anterolateral instability with a minimum follow-up of 15 years. Two techniques were compared: 54 patients had an anatomical reconstruction (AR group) and 45 had an Evans tenodesis (ET group). They were followed up for 19.9+/-3.6 years and 21.8+/-4.6 years, respectively. During follow-up, seven patients in the AR group and 17 in the ET group required a further operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(54 citation statements)
references
References 41 publications
1
51
0
2
Order By: Relevance
“…Krips has reported that after 30 years the Evans tenodesis did not adequately prevent laxity, thus allowing development and progression of osteoarthritis of the ankle and subtalar joints [20].…”
Section: Discussionmentioning
confidence: 99%
“…Krips has reported that after 30 years the Evans tenodesis did not adequately prevent laxity, thus allowing development and progression of osteoarthritis of the ankle and subtalar joints [20].…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic US imaging was previously used to measure abnormalities and motion distances on Kager's fat pad 1,6,7,9 and other soft tissue. 14,15 Still images were extracted from video scans to measure sliding distance offline.…”
Section: Methodsmentioning
confidence: 99%
“…In some cases, the fat pad was observed extending to the soleus muscle. 5 This position means that part of Kager's fat pad may need to be excised during arthroscopic surgery to provide a clear view of the ankle joint, 6 despite the consequence of such excision currently being unclear. Recent studies have highlighted the potential biomechanical importance of the fat pad within the Achilles tendon enthesis organ.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Non-anatomic reconstructions utilize tenodesis fixation to stabilize the ankle with the repair of the native ligaments. While multiple configurations have been described, most techniques involve rerouting of the peroneus brevis around the lateral ankle, and include the Watson-Jones, Evans, and Chrisman-Snook procedures (Figure 3) [74,[79][80][81][82] . Long-term outcomes of non-anatomic reconstructions are hindered by alterations in ankle and hindfoot kinematics and often, resultant loss of subtalar motion [83][84][85][86][87][88][89][90] .…”
Section: Chronic Ankle Instability Treatmentmentioning
confidence: 99%